Seiche in the Gulf of Tonkin - Ninh, Pham Van; Ngoc Duyet, Tran Thi (Vietnam Journal of Mechanics, 1996)
Steichen in the Gulf of Tonkin has been studied by numerical modelling based on the two-dimensional nonlinear shallow water equations system with liquid boundary condition given in the form of forced oscillation. The main proper periods have been defined as follows: 23-25 hours, 1-12 hours, 5-7 hours, 2-4 hours. Among them the 23 hours period is the most evident. The obtained results coincide with observed ones at the long shore hydrometeological stations of the Gulf.